PC based physical modelling of Heterojuction Bipolar Transistor / Sharifuddin Alaluddin - Alaluddin, Sharifuddin (1995)
A PC based physical modelling of AlGaAs/GaAs Heterojunction Bipolar Transistor (HBT) is used to investigate physical processes which have an impact on device performance. A Drift-Diffusion modelling has been employed and Turbo Pascal is used in its implementation. The programme incorporates Fermi-Dirac statistics, electric field dependent mobilities and Shockley-Read-Hall recombinations. The Scharfetter-Gummel expressions for both electron and hole current densities are used. The simulation can be used to study the influence of conduction band spike, recombination effects and junction misalignment on current voltage characteristics.